The Impact of Macroeconomic Factors on Manufacturing Sector Value Added in Ethiopia: An Application of Bounds Testing Approach to Cointegration - Dagim Tadesse Bekele (Universitas Hayam Wuruk Perbanas, 2020)
The role of the manufacturing sector for the economic growth and structural change is very low in Ethiopia and performing less compering with that of the other sectors in the economy. So, this research tried to look at how different macroeconomic variables affect the manufacturing sector value added by using annual time series data from 1982 to 2018 estimated by Autoregressive-Distributed Lag (ARDL). The result from the Bound test shows manufacturing sector value added has a long-run relationship with macroeconomic variables in the model. In the long-run, general inflation rate, exchange rate, and trade openness have a significant negative effect on the manufacturing sector value-added. In contrast, general government expenditure has a significant positive effect. Also, the Error Correction model shows an adjustment towards the long-run equilibrium of the manufacturing sector value-added. So, the government has to control the general inflation level, promote demand for domestic manufacturing products and competitiveness of domestic firms, and strengthen the backward link of the sector to decrease its import-input dependency to reduce the effect of exchange rate depressions. Lastly, effective and efficient government expenditure will have to be used to increase the manufacturing sector value-added.